Chenopodium botrys extract: The preventive effects on the hepatotoxicity induced by Adriamycin: Chenopodium botrys and ethanol toxicity - Mohebbati, Reza; Salami, Fatemeh; Ansari, Fatemeh; Amiri, Mohammad Sadegh (Iranian Journal of Pharmaceutical Sciences, 2026)
Adriamycin, as a drug, is known to induce hepatotoxicity at high doses. This study investigated the preventive effect of Chenopodium botrys extract on Adriamycin-induced liver damage in rats. Twenty-four rats were randomly divided into control, Adriamycin, and prevention groups, including the extract of Chenopodium botrys combined with Adriamycin and silymarin combined with Adriamycin. The experimental period was 30 days. Ultimately, blood was drawn, and liver tissue was removed for evaluation of oxidation markers and biochemical analysis. Administration of Chenopodium botrys significantly decreased the biochemical parameters related to liver function, including alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP), compared to the Adriamycin group. Oxidative parameters, including total thiol content, superoxide dismutase (SOD), and catalase, were improved in the preventive groups compared to Adriamycin in liver tissues. The data confirm that Adriamycin induces hepatic oxidative stress and liver damage. At the same time, co-treatment with the Chenopodium botrys effectively attenuates these adverse effects by restoring redox balance and preserving liver integrity. These findings highlight the therapeutic potential of natural antioxidants in preventing Adriamycin-induced hepatotoxicity.